2008
DOI: 10.1016/j.aca.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition and volatile compounds of caviar from farmed white sturgeon (Acipenser transmontanus)

Abstract: ; Phone: 0039 02 50315759;Caviars are the salt-cured and preserved eggs of many sturgeon species that have been separated from the supporting connective tissue. The most famous and valuable caviars are produced from harvested sturgeons in the area of Caspian Sea, namely Beluga (Huso huso), Osetra (Acipenser gueldenstaedtii) and Sevruga caviar (Acipenser stellatus). Over the past few decades, owing to the strong demand for sturgeon caviar, the over-exploitation of natural stocks has led to a dramatic decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
82
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 57 publications
16
82
0
1
Order By: Relevance
“…The proximate composition of the beluga roe, both cultivated and wild, were within the range reported for sturgeon roe by other researchers (Table 1) [25,26]. However the fatty acid profile of the cultivated and wild sturgeon roes was different and it is likely that the reduced levels of polyunsaturated fatty acids negatively affected fertilization ratio in the cultivated beluga sturgeon.…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rsupporting
confidence: 51%
“…The proximate composition of the beluga roe, both cultivated and wild, were within the range reported for sturgeon roe by other researchers (Table 1) [25,26]. However the fatty acid profile of the cultivated and wild sturgeon roes was different and it is likely that the reduced levels of polyunsaturated fatty acids negatively affected fertilization ratio in the cultivated beluga sturgeon.…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rsupporting
confidence: 51%
“…Most of the aldehydes detected in cooked silver carp were n-aldehydes, most of which were derived from the oxidation of the double carbon-carbon bond of unsaturated fatty acids present in fish flesh, predominantly n-6 or n-9 PUFA or monosaturated fatty acids (MUFA) [12]. It has been reported that hexanal, heptanal, octanal and nonanal are generated from oleic acid and linoleic acids [13]. n-Alkanals from hexanal to decanal are aromatics and provide aspects of grassy, green and fatty (hexanal; threshold 4.5 ppb), fatty and citrus (heptanal; threshold 3 ppd), fatty, soapy and green (octanal; threshold 0.7 ppb), fatty, citrus and green (nonanal; threshold 1 ppb) and fatty and grass (decanal; threshold 0.7 ppb) [14].…”
Section: Discussionmentioning
confidence: 98%
“…The mass spectrometer scanned masses from m/z 33 to 400. Retention indices (RI) of the compounds' relative mixture of n-alkanes (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were determined. Identification of the compounds was based on a comparison of (1) the RI with that of the standard or with those reported in the literature; (2) mass spectra with those in the database of NIST 98 and Wiley 6.0.…”
Section: Analysis Of Volatile Compoundsmentioning
confidence: 99%
“…In terms of dry matter in both samples, only salt content made difference for caviar. Caprino et al (2008) have reported moisture, total lipid, crude protein and ash in caviar of fish that fed with soybean oil+fish oil combination as; 54.41%, 11.04%, 25.39% and 3.79% respectively.…”
Section: Resultsmentioning
confidence: 99%